THE EFFECTIVENESS OF KNOW WHAT LEARNER IMPROVES STUDENTS’ READING HABITS ON READING COMPREHENSION OF PBL- BASED LEARNING RECOUNT TEXTS IN 8TH GRADE OF JUNIOR HIGH SCHOOL 7 PEKANBARU - Mirawati Mirawati (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The importance of increasing understanding of increasing understanding of literacy habits is increasing along with the development of the current digital era. For this reason, the problem of student’s literacy habits needs special attention. Of course, with method-based learning, the TAI method and KWL strategy,videos animasi, Ice Breaking are as intervention in this research because these methods have been proven to have an impact on increasing literacy habits. So, this research aims to: 1) improve student’s reading habits. 2). increase student;s interest in reading recount text. 3). Can increase student’s knowledge in composing words. 4). Student’s can translate simple English sentences. The research was carried out with a PTK design consisting of two cycles and each cycle consisting of one meeting. The result of the research showed that teacher skills increased from an average score (good) in cycle one, then increased to (very good) in cycle two. The percentage of completion of literacy habituation learning in reading comprehension increased from 70 % in cycle one to 90 % in cycle two. The conclusion of this research is that the KWL strategy and videos animasi, Ice Breaking can improve teacher skills, student’s activities and learning outcomes.